2013
DOI: 10.1021/la304768f
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Nanosized Ordered Domains in DOPC/DPPC and DOPC/Ch Binary Lipid Mixture Systems of Large Unilamellar Vesicles Using a TEMPO Quenching Method

Abstract: Nanosized ordered domains formed in 1,2-dioleoyl-sn-glycero-3-phosphocholine/1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DOPC/DPPC) and DOPC/cholesterol (Ch) liposomes were characterized using a newly developed (2,2,6,6-tetramethylpiperidin-1-yl)oxyl (TEMPO) quenching method. The membrane fluidity of the DOPC/DPPC liposomes, evaluated by the use of 1,6-diphenyl-1,3,5-hexatriene (DPH), increased significantly above their phase-transition temperature. The fluorescence spectra of 6-lauroyl-2-dimethylamino naphth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
227
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(237 citation statements)
references
References 51 publications
10
227
0
Order By: Relevance
“…TNS and Laurdan are polar probes, and their emission peaks were blue shifted and their fluorescence intensities increased in proportion to the hydrophobicity of the solvents [27,[29][30]. In the presence of liposomes, the ranges of the TNS emission wavelengths were 438-446 nm, indicating that TNS is inserted at water-membrane interface regions (: [25][26][27][28][29][30][31][32][33][34][35]. Furthermore, the intensity of TNS fluorescence was higher in the 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) liposome, while it was lower in the 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) liposome at 25 °C, indicating that the membrane surface of DOPC was more hydrophobic than that of DPPC.…”
Section: Methods For Characterizing Micro-/nano-domain Structure On LImentioning
confidence: 99%
See 1 more Smart Citation
“…TNS and Laurdan are polar probes, and their emission peaks were blue shifted and their fluorescence intensities increased in proportion to the hydrophobicity of the solvents [27,[29][30]. In the presence of liposomes, the ranges of the TNS emission wavelengths were 438-446 nm, indicating that TNS is inserted at water-membrane interface regions (: [25][26][27][28][29][30][31][32][33][34][35]. Furthermore, the intensity of TNS fluorescence was higher in the 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) liposome, while it was lower in the 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) liposome at 25 °C, indicating that the membrane surface of DOPC was more hydrophobic than that of DPPC.…”
Section: Methods For Characterizing Micro-/nano-domain Structure On LImentioning
confidence: 99%
“…It is concluded that the surface properties of liposome membranes can be monitored using TNS (: 25-35), Laurdan (: 5-30), and DPH (: 4-6), and the characteristics of each probe is summarized in Table 3 and Figure 3. It has been recently reported that the nano-ordered domain can be detected by using the newly developed 2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPO) quenching method [34]. As an example, Figure 4 shows a summary of the physicochemical properties of DOPC/DPPC/Ch binary or ternary lipid mixtures through a schematic illustration of nano-sized ordered domains in LUV.…”
Section: Methods For Characterizing Micro-/nano-domain Structure On LImentioning
confidence: 99%
“…4. The yields for systems (II), (III), and (IV) were as good as that of the conventional vesicle preparation method (i.e., the yield of DPPC vesicles using the thin-film hydration method 22,34 was 92.8 6 3.0%; although a small amount of lipid film existed in the round bottom flask in our experiment). In contrast, the yield for system (I) was lower than the other conditions, and an insoluble lumpy lipid aggregate was observed in the sample.…”
Section: B Lipid Concentration Of the Vesicles Prepared At Differentmentioning
confidence: 50%
“…Fluorescent probe Laurdan is sensitive to the polarity around itself, which allows the surface polarity of lipid membranes to be determined. 21,22,31 Laurdan emission spectra exhibit a red shift caused by dielectric relaxation. Thus, emission spectra were calculated by measuring the general polarization (GP 340 ) for each emission wavelength as follows:…”
Section: E Evaluation Of the Membrane Properties Of Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation